2012
DOI: 10.1002/nbm.2801
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of kinetic models for analysis of pyruvate‐to‐lactate exchange by hyperpolarized 13C NMR

Abstract: The activity of specific enzyme-catalyzed reactions may be detected in vivo by 13C NMR of hyperpolarized (HP) substrates. The signal from HP substrates and products, acquired over time, have been fit to a number of different mathematical models to determine fluxes, but these models have not been critically compared. In this study, two-pool and three-pool first-order models were constructed to measure flux through lactate dehydrogenase in isolated glioblastoma cells by NMR detection of lactate and pyruvate foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
132
3

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 104 publications
(144 citation statements)
references
References 35 publications
9
132
3
Order By: Relevance
“…When a non-selective excitation pulse was applied, a summation of spectra revealed labeling of lactate C1 (Fig. 4A), as previously reported for these cells (31). Labeling in alanine C1 and in C1 of pyruvate hydrate was also detected, but H[…”
Section: A Selective Pulse Technique To Maximize Detection Of Pyruvatsupporting
confidence: 81%
See 4 more Smart Citations
“…When a non-selective excitation pulse was applied, a summation of spectra revealed labeling of lactate C1 (Fig. 4A), as previously reported for these cells (31). Labeling in alanine C1 and in C1 of pyruvate hydrate was also detected, but H[…”
Section: A Selective Pulse Technique To Maximize Detection Of Pyruvatsupporting
confidence: 81%
“…Acquisition of spectra was initiated immediately and proceeded for ϳ3.5 min (see "Hyperpolarization, Shaped Pulse, and NMR Spectroscopy in Intact Cells" below for details on cell transfer and conditions for the hyperpolarization experiment). We previously reported that cells subjected to trypsinization and hyperpolarized [1][2][3][4][5][6][7][8][9][10][11][12][13] C]pyruvate maintain rates of LDH flux similar to rates of adherent cells (31). To protect against depletion of oxygen from the medium during trypsinization and preparation of the cell suspension, the medium was mixed frequently, including immediately before transfer of the cells to the NMR tube, which occurred within a few seconds of introduction of [1][2][3][4][5][6][7][8][9][10][11][12][13] C]pyruvate.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations